Ecologies of care in times of climate change: Water security in the global context - Buser, Michael (Bristol Bristol University press, 2024)
This book investigates places in Europe, North America and Asia that are facing the immense challenges associated with climate change adaptation. Presenting real-world cases in the contexts of coastal change, drinking water and the cryosphere, Michael Buser shows how the concept of care can be applied to water security and climate adaptation.
Keywords: Climatic changes Asia; Water security; Global Warming & Climate Change